Affective practice architectures of professional learning in international schools. Issue 2 (4th May 2022) - Kostogriz, Alexander; Adams, Megan; Bonar, Gary
ABSTRACT: This article focuses on practice architectures of international schools that create affective atmosphere for the professional learning and becoming of international-hire and local-hire teachers. We use the concept of precarious labour to explore relational tensions and their effects on the professional learning of teachers and school leaders. Empirical data are drawn from two case study schools located in two major countries that offer international education. The data sets include interviews with school leaders and international and 'local' teachers. The analysis focuses on relational tensions experienced by teachers in these schools. The article argues that the affective atmosphere of teacher workplaces produces a force – a sense of precariousness – that envelopes teachers and oppresses them. At the same time, it also provides the very conditions for their professional learning in international workplaces. From this practice-ontological perspective, therefore, it is important to recognise the primacy of affect in the professional learning of teachers.